Zircon U–Pb and Sm–Nd geochronology and geochemistry of the Sn–W deposits in the northern Guposhan ore field, Nanling Range, southern China - Cao, Jingya; Yang, Xiaoyong; Lu, Youyue; Fu, Jianming; Yang, Lizhi (Ore geology reviews, 2020)
[Display omitted] •Zircon and cassiterite U–Pb isotopic dating obtained Permian age of granites related the Sn mineralization in the Eastern Belt of Peninsular Malaysia.•I-type granites are identified by partial melt of the Proterozoic meta-igneous rocks.•Granites were formed in the island-arc environment of an active continental margin. The Guposhan ore field, located in the central part of the Nanling Range and close to the giant Central South Peninsula tin ore belt, is well-known for its large-scale Sn (W) mineralization and hosts a series of middle to large scale Sn (W) deposits. In this study, medium to fine grained biotite granite, outcropped in the mining area, have zircon U–Pb ages of 162.8 ± 1.3 Ma (MSWD = 0.54) and 162.7 ± 1.2 Ma (MSWD = 0.66), respectively. These zircon ages are consistent to the Sm–Nd isotopic age of minerals (garnet, hornblende, clinopyroxene and orthopyroxene) from the skarn-type ores, which is 160.4 ± 4.8 Ma (MSWD = 1.3). These granites are characterized by high content of SiO2, K2O, Na2O and REEs, and high Ga/Al ratios, indicating that they belong to highly fractionated A-type granites with high-K calc-alkaline and aluminous-peraluminous signatures. The zircon Lu–Hf isotopes of these granites have εHf(t) values and TDMC ages of −2.66 to −1.71 and 1.32–1.38 Ga, respectively. Combined with the previous studies, it was proposed that the magma was formed by the mixing of crust-mantle components (ca. 50 and ca. 50%, respectively). In addition, magmas are characterized by low temperatures of ca. 710 °C and oxygen fugacity (log(fO2) values of −18.5 to −16.4. Formation of these granites were likely related to an intraplate extensional tectonic setting, triggered by roll-back of the subducted Paleo-Pacific plate beneath the South China Block (SCB). These granites are in favor of the Sn (W) mineralization, making the Guposhan ore district a large-scale Sn (W) mineralization ore field in the Nanling Range.